Young children's agency with digital technologies. (10th October 2021) - Nolan, Andrea; Edwards, Susan; Salamon, Andi; Straker, Leon; Grieshaber, Susan; Skouteris, Helen; Henderson, Michael; Highfield, Kate; Bartlett, Jacinta
Abstract: This paper examines the evidence of children's agency in research about infants, toddlers and technologies. It finds that an implicit reliance on technological determinism as a theoretical perspective for positioning technologies relative to young children's development tends to shape research in terms of understanding the impact of technologies on young children. Drawing on critical constructivism as a philosophical stance on technologies, this paper argues that children's agency with technologies may be further investigated in terms of practice architectures to better understand the social mediation of infant and toddler interactions and engagements with technologies.